2013
DOI: 10.3324/haematol.2012.073833
|View full text |Cite
|
Sign up to set email alerts
|

Elevated lipoprotein (a), small apolipoprotein (a), and the risk of arterial ischemic stroke in North American children

Abstract: Lipoprotein (a) is a risk factor for adult cardiovascular events, in which the apolipoprotein (a) component is thought to promote atherogenesis and impair fibrinolysis. We investigated whether elevated plasma lipoprotein (a) concentration and small predominant apolipoprotein (a) isoform size (number of kringle-4 domains) are risk factors for childhood arterial ischemic stroke and correlate with plasma fibrinolytic function. Patients who had had an arterial ischemic stroke in childhood (29 days -<21 years at on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 28 publications
0
29
3
1
Order By: Relevance
“…16,17 In contrast to the reported HR of 14.0 at 36 months in 1 study, 17 we report a lower HR of 2.6 for adult stroke survivors with elevated Lp(a) levels of >30 mg/dL at 12 months. The difference in relative risk of recurrent events remains unexplained; however, the increased risk of younger versus older patients with stroke might be explained because of the low absolute risk of young individuals and differences in study design.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…16,17 In contrast to the reported HR of 14.0 at 36 months in 1 study, 17 we report a lower HR of 2.6 for adult stroke survivors with elevated Lp(a) levels of >30 mg/dL at 12 months. The difference in relative risk of recurrent events remains unexplained; however, the increased risk of younger versus older patients with stroke might be explained because of the low absolute risk of young individuals and differences in study design.…”
Section: Discussioncontrasting
confidence: 53%
“…Only 2 prospective studies exist that assessed the risk of recurrent ischemic stroke events in children. 16,17 Both studies indicated that elevated Lp(a) levels were associated with a 4-to >10-fold increase in risk of recurrent stroke.…”
mentioning
confidence: 99%
“…For example, many studies of Lp(a) used a cutoff of .0.3 mg/dL. 34,35 In contrast, our results found that the normal range in controls extended far above this number, with no differences observed between cases and controls. Finally, another highly powered study of perinatal stroke thrombophilia submitted for publication also describes a similar lack of association between known thrombophilias and perinatal stroke (L. Lehman, personal communication, 11 October 2016).…”
Section: Discussioncontrasting
confidence: 56%
“…In other words, elevated Lp(a) may affect the penetrance of procoagulant thrombophilic risk factors. One recent study reported that elevated Lp(a) was associated with risk for recurrent, but not incident, stroke (137). Another study found no relationship between elevated Lp(a) and thromboembolism (of either venous or arterial origin) in Thai children (138).…”
Section: Childrenmentioning
confidence: 96%